Banco Industrial - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la fachada del Banco Industrial en un edificio de tres niveles al frente de la plaza de armas, actualmente funciona la entidad de la Derrama Magisterial - MinEdu.
ENGLISH: The façade of the Banco Industrial was observed in a three-story building in front of the main square, which currently houses the entity of the Derrama Magisterial - MinEdu.

SPANISH: Se observo la fachada del Banco Industrial en un edificio de tres niveles al frente de la plaza de armas, actualmente funciona la entidad de la Derrama Magisterial - MinEdu.
ENGLISH: The façade of the Banco Industrial was observed in a three-story building in front of the main square, which currently houses the entity of the Derrama Magisterial - MinEdu.
Industrial Banking
Keywords: Iquitos (Perú)|~|Banks|~|Banking system|~|Iquitos (Perú)|~|Banco|~|Perú|~|Sistema bancario y banca|~|Banco|~|Iquitos (Perú)|~|Banco|~|Perú|~|Banking system and banking|~|Bank